Pelvic exenteration for locally advanced and local recurrent primary rectal cancer: a 5 years Asian retrospective cohort study and lessons to learn - Leow, Yeen Chin; Henry, Fitjerald; Lee, Fei Yee (International Surgery Journal, 2020)
Background: Locally advanced rectal cancer (LARC) and local recurrent rectal cancer (LRRC) were deemed incurable, but with surgical advancement, pelvic exenteration has emerged as a curative option. Although colorectal cancer cases are common, pelvic exenterations are limited to several centres in Malaysia. The study aimed to determine the outcomes of pelvic exenteration from the centre in terms of complete resection, local recurrence rate, mortality rate and complications rate. Methods: Retrospective data collection was done for pelvic exenteration surgeries of LARC and LRRC from year 2014 till 2018 in a Malaysian tertiary referral centre. Demographic data, types of pelvic exenteration, postoperative complications, postoperative histopathology for complete resection (R0) and local recurrence were collected from the hospital medical records. Results: From 2014 till 2018, 51 cases of pelvic exenteration were done, with a mean age of 55.8±12.4 years and predominance of male gender (55%). Thirty-four cases (66.7%) completed the exenteration. A mere 24 cases (47.1%) had complete preoperative imaging of computed tomography (CT scan), pelvic magnetic resonance imaging (MRI) and positron emission tomography-computed tomography (PET/CT) scan. R0 resection was achieved in 23 cases (67.6%). Complications were found in 44.8% of patients including anastomotic leak, collection, surgical site infection or cardiac/lung complications. The 30-days postoperative mortality rate is 3.9%. The six-months local recurrence rate was 5.8% and one-year local recurrence rate was 7.8%. Conclusion: Pelvic MRI and PET-CT scan is suggested to be compulsory for all pelvic exenteration candidates to ensure a good outcome. Multidisciplinary team approach is needed preoperatively to discuss the feasibility of pelvic exenteration to optimise the outcomes of this surgery.